PHOTODEGRADATION OF METHYL ORANGE USING TiO2 CATALYST SUPPORTING POROUS CERAMIC - Taufiq, Muhammad; Hasri, Hasri; Pratiwi, Diana Eka; Rahman, Abd; Putri, Suriati Eka (Indonesian Journal of Fundamental Sciences, 2025)
The purpose of this study was to determine the effect of initial pH and concentration of methyl orange (MO) dye solution on the photodegradation process using a TiO2 catalyst impregnated into porous ceramics. This research is an experimental research consisting of several stages, namely; preparation  of Pinrang natural clay  samples, synthesis of porous ceramics using the gelcasting method, impregnation of TiO2 catalysts into porous ceramics by  the sol-gel coating method, and analysis of the influence of initial pH and concentration of MO dyes on photodegradation using impregnated TiO2 catalysts in porous ceramics. The analysis of the effect of the initial pH showed that the higher the pH of the MO dye, the lower the percentage of dye degradation as well as the concentration value, the higher the MO concentration value, the lower the percentage of dye degradation. The optimum degradation was obtained at pH 3 and a concentration of 10 ppm with a degradation percentage of 75.15%.